Characteristic of Blended Fuel Properties and Engine Cycle To-Cycle Variations with Butanol Additive - Obed M., Ali; R., Mamat; Nik Rosli, Abdullah; Abdul Adam, Abdullah (2014)
Biodiesel fuel characteristics are one of the most important parameters that limited their application in diesel engines. Though biodiesel-diesel blended fuel can replace diesel satisfactorily at low blending ratios up to 20%, problems related to fuel property persist at high blending ratio. Hence, in the present study, the feasibility of biodiesel-diesel blended fuel B30 was investigated with respect to its properties and engine cyclic variations with increasing butanol additive. The blended fuel with additive were tested experimentally in a diesel engine and the in-cylinder pressure data were collected and analyzed using the coefficient of variation and wavelet power spectrum to evaluate the engine cyclic variations compared to diesel fuel engine test results. The fuel property test results showed slight improvement in density and acid value with significant reduction in viscosity when increasing butanol additive. Furthermore, the blended fuel pour point was reduced to −6 °C at 8% butanol additive. On the other hand, the energy content slightly affected with increasing butanol additive in the blend. From the wavelet power spectrum, it is observed that the short-period oscillations appear intermittently in pure blended fuel, while the long and intermediate-term periodicities tends to appear with increasing additive ratio. Moreover, the spectral power increased with an increase in the additive ratio indicating that the additive has a noticeable effect on increasing the cycle to cycle variation. The coefficient of variation of indicated mean effective pressure for B30 were found to be the lowest and increases with increasing additive ratios. Both the wavelet analysis and coefficient of variation results reveals that blended fuel B30 has engine cyclic variations comparable to diesel fuel with increasing butanol additive up to 4%.